MYELOMENINGOCELE: IMPACTS AND RELEVANCE OF INTRAUTERINE CORRECTION (REMUNOM, 2025)
Introduction: Myelomeningocele (MMC) is a severe malformation, also known as Spina Bifida. This condition is characterized by the failure of the vertebra to close properly, resulting in an opening and exposure of the neural tube, which does not fully form. Objective: To analyze the impacts of intrauterine surgery for the correction of myelomeningocele on patients’ quality of life. Methods: This study is an integrative literature review. The searches will be conducted in the SciELO, BVS, and PubMed databases, in Portuguese and English, using specific descriptors combined with the Boolean operator AND, considering articles published between 2015 and 2024. Results: The selection of 15 articles followed Bardin’s method, with inclusion criteria focused on studies addressing the quality of life of patients undergoing intrauterine or postnatal corrective surgery. Discussion: Folic acid deficiency is the main modifiable factor associated with MMC, and periconceptional supplementation can reduce its incidence by up to 70%. Neurological, motor, and urological symptoms vary according to the level of the spinal lesion, with higher lesions (L1–L2) being associated with more severe motor consequences. MMC is often associated with hydrocephalus, requiring the implantation of a ventriculoperitoneal shunt (VPS), and with neurogenic bladder, which requires urological follow-up. Intrauterine fetal corrective surgery, ideally performed between the 20th and 25th gestational weeks, has shown better neurological and functional outcomes compared to postnatal correction. Conclusion: Although intrauterine surgery carries maternal and obstetric risks, advances in fetoscopic techniques have made the procedure increasingly safe and effective, establishing it as a promising alternative for improving the quality of life of patients with myelomeningocele.